Role and Mechanism of Lactylation in Cancer - Qicheng ZHANG; Limin CAO; Ke XU (Chinese Journal of Lung Cancer, 2024)
Post translational modifications (PTMs) can change the properties of a protein by covalent addition of functional groups to one or more amino acids, and influence almost all aspects of normal cell biology and pathogenesis. Lactylation is a novel identified PTM, and has been found in both histone and non-histone proteins. Since associated with the end product of glycolysis-- lactate, lactylation modification could provide a new perspective for understanding the relationship between metabolic reprogramming and epigenetic modifications. Accumulated evidences suggest that lactylation play important roles in tumor progression and links to poor prognosis in clinical studies. Histone lactylation can affect gene expression in tumor cells and immunological cells, further promoting tumor progression and immune suppression. Lactylation on non-histone proteins can also regulate tumor progression and drug resistance. In this review, we aimed to summarize the roles of lactylation in cancer progression, microenvironment interactions and immune suppression, try to identify new molecular targets for cancer therapy and provide a new direction for combined targeted therapy and immunotherapy.